A study of the ballistic protection mechanism of two kinds of structure against 7.62×54 mm ball ammunition. (March 2020) - Li, G F; Yang, L; Xu, H; Guo, Y Y; Wang, Zh W; Wang, L; Miao, Ch; Wu, Y Ch
Abstract: In this work, the protection mechanism of two kinds of structure was studied using 7.62×54 mm ball ammunition, which still played an important role in the threat spectrum of military vehicles. The tested one structure is consisted with silicon carbide (SiC) ceramic and Ultra-High Molecular Weight Polyethylene (UHMWPE), and the other is UHMWPE only. Silicon carbide ceramic was chose as strike face material for the reason of its widely using in Light Weight Vehicle Armor. And the UHMWPE was widely used for personnel body armor, because of its high protection ability and low density. These two kinds of structure were tested with 7.62×54 mm ball ammunition using a 7.62 mm powder gun launching system. After the ballistic experiment, the target plate was evaluated, and the residual steel core was recovered and measured. It was found that the main effect of ceramic strike face was eroding the steel core, rather than breaking it in the scene of defeating AP round ammunition. Otherwise, there is a critical thickness with the ceramic strike face to erode the steel core in the ceramic/UHMWPE combination, for the reason of the presence of two intermediate parts, the jacket and lead filler, between the core and ceramic target. Furthermore, compared to the ceramic/UHMWPE structure, single UHMWPE laminate is more effective, because that is strong enough to mushroom the core and absorb the energy.